2021
DOI: 10.7150/ntno.51676
|View full text |Cite
|
Sign up to set email alerts
|

Radiolabelling of Extracellular Vesicles for PET and SPECT imaging

Abstract: Extracellular vesicles (EVs) such as exosomes and microvesicles have gained recent attention as potential biomarkers of disease as well as nanomedicinal tools, but their behaviour in vivo remains mostly unexplored. In order to gain knowledge of their in vivo biodistribution it is important to develop imaging tools that allow us to track EVs over time and at the whole-body level. Radionuclide-based imaging (PET and SPECT) have properties that allow us to do so effic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 124 publications
1
31
0
Order By: Relevance
“…Until 1996, these exosomes were considered debris, but since then, studies have reported the role of exosomes in immune responses such as antigen presentation in immune-modulating activity of B cell-derived vesicles and their potential in immunotherapy [123,[126][127][128]. Extensive research has been done in recent years to gain a deeper understanding of these complex vesicles and their involvement in the cellular system, as well as exploration for potential clinical diagnosis and therapeutics in nanomedicine [125,129,130]. Currently, there are studies to investigate the effects of exosomes on SARS-CoV-2 coronavirus and potential development of exosome-based therapeutic approaches to tackle this deadly virus [131][132][133].…”
Section: Radiolabeled Exosomes For Nuclear Imagingmentioning
confidence: 99%
See 3 more Smart Citations
“…Until 1996, these exosomes were considered debris, but since then, studies have reported the role of exosomes in immune responses such as antigen presentation in immune-modulating activity of B cell-derived vesicles and their potential in immunotherapy [123,[126][127][128]. Extensive research has been done in recent years to gain a deeper understanding of these complex vesicles and their involvement in the cellular system, as well as exploration for potential clinical diagnosis and therapeutics in nanomedicine [125,129,130]. Currently, there are studies to investigate the effects of exosomes on SARS-CoV-2 coronavirus and potential development of exosome-based therapeutic approaches to tackle this deadly virus [131][132][133].…”
Section: Radiolabeled Exosomes For Nuclear Imagingmentioning
confidence: 99%
“…Currently, there are studies to investigate the effects of exosomes on SARS-CoV-2 coronavirus and potential development of exosome-based therapeutic approaches to tackle this deadly virus [131][132][133]. Evidently, exosomes play a crucial role not only in elimination of unwanted proteins out of the cell but also in other important cellular communications and functions [122,123,126,127,129,[134][135][136].…”
Section: Radiolabeled Exosomes For Nuclear Imagingmentioning
confidence: 99%
See 2 more Smart Citations
“…91,92 Imaging tools commonly used are single-photon emission computed tomography, positron emission tomography, and magnetic resonance imaging. [92][93][94] It should be remembered that the labeling compounds have a longer half-life than EVs and continue to be detected by imaging even after EVs are degraded. 54,95 Bioengineering the EV membranes with inbuilt markers that degrade simultaneously with the EVs will be useful to avoid false-positive findings Table 2.…”
Section: Evs In Diagnostic Imagingmentioning
confidence: 99%